Business Management App for cattle ranches, articulated with the bovine traceability program - Pérez, Luiyiana; Lasso, Rolando (Ingeniería Solidaria, 2019)
Introduction: The article is the result of Research "Development and implementation of a software for the management and control of livestock farms, articulated with the bovine traceability program". This initiative was financed by SENACYT and carried out at the Universidad Tecnológica de Panamá, Azuero Campus, with the collaboration of Consultant Luiyiana Pérez during 2017 and 2018.Problem: This project arises from lack of producers in the field information registration and bovine traceability program.Objective: To develop an app that allows you to manage the management of livestock farms, integrated to Livestock Management System (SIGEPE in its Spanish acronym) from the agencies of the Ministry of Agricultural Development.Methodology: A study of the level of the digital divide index (IBD) in the sector was carried out; a proportional stratified sampling was used for the selection of the producers and the view-controller model was used to develop the app.Result: A database was created, with information about nutrition, health programs, veterinary products among others. An application was developed, including its respective modules and a training plan for the implementation of the app.Conclusion: The livestock business competitiveness vs. bovine traceability regulation demands the appropriate field information registration at all points of animal production.Originality: The incorporation of livestock control by the various agencies and their articulation with the bovine traceability.Limitations: The users´ deficient technological skills in the management and use of ICTs.
Keywords: Growing Complexity; Organizational Structure; Information Processing Systems